Antineutrophil Cytoplasmic Autoantibody-Associated Glomerulonephritis as a Complication of Home Parenteral Nutrition - Flogelova, Hana; Karaskova, Eva; Bouchalova, Katerina; Rohanová, Marie; Latalova, Vendula; Tichy, Tomas; Tesar, Vladimir (Case reports in nephrology and dialysis, 2022)
Patients on long-term home parenteral nutrition (HPN) occasionally develop glomerulonephritis due to chronic central venous catheter (CVC)-related infection. Most previously reported cases were membranoproliferative glomerulonephritis (MPGN). This is a case report of a 16-year-old girl receiving HPN for short bowel syndrome. After 11 years on HPN, she developed acute kidney injury with macroscopic hematuria, nephrotic-range proteinuria, and a reduced glomerular filtration rate (GFR). Initially, MPGN associated with chronic bacteremia was suspected with the assumption that the condition would be treated with antibiotics and CVC replacement. However, her kidney biopsy revealed antineutrophil cytoplasmic autoantibody (ANCA)-associated glomerulonephritis (AAG). This was consistent with the fact that the patient tested positive for proteinase 3-ANCA. Immunosuppressive therapy with methylprednisolone pulses (followed by oral prednisone) and rituximab led to remission. Her GFR and protein excretion returned to normal. Chronic bacteremia as a complication of long-term HPN may cause various types of glomerulonephritis including, rarely, AAG requiring immunosuppressive therapy.